Isolation and Spatial Structure of 5,7-Dihydroxy-6,3′,4′-Trimethoxyflavone - Turdybekov, K.M.; Rakhimova, B.B.; Makhmutova, A.S.; Gatilov, Y.V.; Adekenov, S.M. (Eurasian Journal of Chemistry, 2023)
The article presents the results of a chemical study of semi-dry wormwood (Artemisia semiarida), an endemic plant of Kazakhstan. The amount of extractive substances was obtained by extraction with chloroform from air-dried crushed above-ground part of the plant collected in the vegetative phase. The compound was isolated using a column chromatography method. Silica gel of the KSK brand was used with the ratio of the sum of substances – carrier = 1:10. When the column was eluted with a 13:7 petroleum ether – ethyl acetate mixture, a yellow crystalline substance of the composition C18H16O7 with m.p. 234–237° C was obtained (recrystallization from ethyl acetate). The structure of the obtained compound (5,7-dihydroxy-6,3′,4′-trimethoxyflavone or eupatilin) was established by analysis of IR and NMR spectra. The spatial structure of eupatilin was determined by X-ray diffraction. In the crystal structure of 5,7-dihydroxy-6,3′,4′-trimethoxyflavone the rotation of the phenyl ring relative to the main framework (chromene ring) was found to be only 4.1°. Four conformers with different rotations of the phenyl ring (the torsional angles of O1C2C1′C2′ are 30°, 140°, 210° and 320°, respectively) and small energy barriers (about 8.4 kJ/mol) can be realized in the free state of the molecule.
Keywords: NMR spectroscopy; IR spectroscopy; X-ray analysis; quantum chemistry; Artemisia semiarida; endemic; 5,7-dihydroxy-6,3′,4′-trimethoxyflavone; eupatilin; phenolic compounds